Vpliv podnebnih sprememb na pričakovano prostorsko prerazporeditev tipov gozdne vegetacije - Kutnar, Lado (Zbornik gozdarstva in lesarstva, 2009)
The redistribution of forest vegetation types in Slovenia, driven by the expected climate change, has been simulated. The potential spatial changes of forest vegetation have been analyzed using empirical GIS model forecasting thespatial distribution of forest vegetation in relation to climate and other ecological parameters. Based on the three different climate scenarios, the simulations showed that the spatial pattern of forest vegetation will be altered under the impacts of climate change. According to the prediction in the year 2070, the vegetation type is likely to be changed on more than 75% ofall forest sites. Nowadays dominant forests, mostly beech, may be affected by such changing environmental conditions. The decrease of the actual prevailing mesic beech forest share from the present 57% to only 3% under the pessimistic scenario and up to 29% under the optimistic scenario could be expected. In a warmer climate, predicted by all three future scenarios, different thermophilous forests will be expanded over larger area of the country
Keywords: gozdovi; klimatske spremembe; modeli; Slovenia; Slovenija; vegetacija